2002
DOI: 10.1007/s00259-002-0780-y
|View full text |Cite
|
Sign up to set email alerts
|

18F-FDG and 18F-FET uptake in experimental soft tissue infection

Abstract: The aim of this study was to compare the uptake of (18)F-fluoroethyl- L-tyrosine ((18)F-FET) with that of (18)F-fluorodeoxyglucose ((18)F-FDG) in activated inflammatory white blood cells. Unilateral thigh muscle abscesses were induced in 11 rats by intramuscular inoculation of 0.1 ml of a bacterial suspension ( S. aureus, 1.2 x 10(9) CFU/ml). Four animals were intraperitoneally injected with 130-180 MBq (18)F-FDG, four with 140-170 MBq (18)F-FET and three with a mixture of 140-170 MBq (18)F-FET and 1.8 MBq (14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
48
0
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(52 citation statements)
references
References 9 publications
1
48
0
3
Order By: Relevance
“…18 F-FET transport in F98 glioma cells, however, is shared by serine, which is a substrate of LAT2 but not of LAT1 (20). At the same time, 18 F-FET shows no uptake in inflammatory tissue where LAT2 is not expressed (31,35). Therefore, it remains unclear whether the different results in both papers can be attributed to the particular tracer uptake or if they were caused by different study methodology.…”
Section: Discussionmentioning
confidence: 43%
“…18 F-FET transport in F98 glioma cells, however, is shared by serine, which is a substrate of LAT2 but not of LAT1 (20). At the same time, 18 F-FET shows no uptake in inflammatory tissue where LAT2 is not expressed (31,35). Therefore, it remains unclear whether the different results in both papers can be attributed to the particular tracer uptake or if they were caused by different study methodology.…”
Section: Discussionmentioning
confidence: 43%
“…In addition to binding to glioma cells, TSPO tracers bind to myeloid cell lines, including glioma-associated microglia and macrophages (18). In contrast, uptake of 18 F-FET is not increased in areas of infiltrating activated macrophages and activated microglia in experimental abscesses (4,19). It may be hypothesized that TSPO-negative but 18 F-FET-positive areas represent primarily reactive astrocytosis, predicting a less aggressive development, but biopsy control confirmation is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Animal experiments have shown that 18 F-FET, in contrast to 18 F-FDG and 3 H-methyl-L-methionine ( 3 H-MET), exhibits no uptake in inflammatory cells and in inflammatory lymph nodes, promising a higher specificity for the detection of tumor cells (13)(14)(15)(16). Nevertheless, increased uptake of 18 F-FET has been observed in single cases of brain abscesses and in a demyelinating process (17).…”
mentioning
confidence: 99%